Mini Tinjauan Literatur Pemanfaatan Software Math Editor untuk Berpikir Komputasi Siswa - Siti Nurmala Sirait; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to examine the role of Math Editor software in developing students' computational thinking skills in mathematics learning. Computational thinking is an important skill that involves the process of solving problems logically, systematically, and efficiently. This study adopts a literature review approach by analyzing literature related to the use of Math Editor as a supporting medium for the mathematical thinking process. The results of the study indicate that the use of Math Editor not only makes it easier to compile mathematical expressions, but also strengthens analytical thinking skills, increases accuracy, and encourages students' independent reflection. In addition, the integration of Math Editor into a digital learning platform expands opportunities for the development of interactive and collaborative learning. Thus, this software has great potential in supporting technology-based mathematics learning.